Health System Resilience and Community Participation amidst the Covid 19 Pandemic: A Case Study of SONJO (Sambatan Jogja) in the Special Region of Yogyakarta, Indonesia - Ganjar Widhiyoga; Nuri Ikawati (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2022)
There is a growing concern over how the Covid-19 pandemic might affect low- and medium- income countries (LMOCs) worse compared to high-income countries. The main contributor to this aggravation is the health system is not strong enough to sustain the shock the system caused by the pandemic. Therefore, strengthening the health system resilience in LMOCs is imperative to lessen the gap between countries. The health system resilience constitutes a set of capabilities to maintain shocks, adapt to the shock and transform into actions to keep the essential functions of the health system. The essential factor contributing to the resilience of a health system is the recognition of the complexity and dynamic power relationship underlying the system, including opening access for community participation. This study aims to describe how SONJO, a community-based organization in the Special Region of Yogyakarta (SRY), Indonesia, has played a crucial role in strengthening the health system resilience in the province during the Covid-19 pandemic 2021. As the nature of the research, this study conducts a qualitative approach to collect and analyze the data. The study shows that SONJO can develop adaptive mechanisms to cope with the outbreak through the collective action of diverse actors in the health system translated from shared knowledge, coordination, and values. SONJO acts as a social broker that bridges a wide range of actors in the health system of SRY through a digital platform.